Pelatihan “How to Build Resilience at Work” pada Karyawan Puskesmas X di Mojokerto - Dhemosa Kresnayutiana Rengasti; Athiyyah Rafi Razani; A. Johanes Tjahjoanggoro; Saras Dwi Anugrah Putri Kasnadianto (I-Com: Indonesian Community Journal, 2025)
UPT Puskesmas X is a community health center with the highest accreditation level, "paripurna." Currently, its employees are burdened by several issues that have led to a decline in work performance, subsequently affecting the quality of services provided. To address this, the researcher implemented a training program aimed at enhancing employee resilience. The results showed a significant improvement in resilience following the training (t = 0.002, p < 0.05). A follow-up conducted two weeks after the training indicated no significant change compared to the immediate post-training results.